Estimating a Spectral Correlation Function under the Conditions of Imperfect Relation between Signal Frequencies and a Sampling Frequency - Sebesta, Vladimir (Společnost pro radioelektronické inženýrství, 2010)
This paper is devoted to the estimation of the spectral correlation function. The examined signal is a simple DSB-SC signal. The aim of the paper is discovering events connected with nonstandard relations between signal frequency parameters and sampling frequency. They manifest by descending the spectral correlation function modulus. The events has been described analytically and verified using computer experiments. It is shown, that influence of the inaccuracy of the frequency is stronger for modulating frequency than for carrier frequency. Small inaccuracies of the frequencies have acceptable consequences.
Keywords: Spectral correlation function; feature detector; cyclic frequency; spectral frequency; frequency offset